Prevalence and associated factor for positive chest x-ray during tuberculosis screening among high risk groups in Kedah - Shushami , Ahmad Hanis Ahmad (2017)
Tuberculosis screening program among high risk groups using chest xray have been implemented by Ministry of health Malaysia but the case detection are not encouraging. More prioritization is needed to identify factors that contribute to a chest x-ray screening positive so that the positive cases would not be missed and may help in halting the chain of transmission of TB in the society. This was a cross sectional study involving patients who were screened during TB screening for high risk groups in Kedah in 2016. The patients involved were from the list that has been included in the TB information system (TBIS) 104 A which is a notification system for this screening. The study involved 1417 people involving facilities which were randomly selected from six regions that were also selected randomly. Data analysis was conducted using SPSS version 22 for descriptive and inferential analysis. Simple logistic regression analysis and multiple logistic analysis was used to identify factors associated with chest x-ray result at p-value of <0.05 in the final model. In this study, most of the people involved were at their late adulthood. The mean (SD) of age was 49.19 (18.2) years. Male accounts for 726 people (51.2%). Majority of the sample population were Malaysian 1298 (91.6%) which comprise of Malay 1024 (72.3%) followed by Indian 139 (9.8%), Chinese 122 (8.6%) and other races 13 (0.9. Majority of the sample population were asymptomatic 1036 (73.1%). Diabetes were the largest proportion of risk group screened 638 (45.0 %), followed by contact 334 (23.6%), ‘others unspecified’ 204 (14.4%), institutionalised 124 (8.8), clients of quit smoking clinic 57 (4.0%), End Stage Renal Failure/Chronic Obstructive Airway Disease 33 (2.3%) and lastly HIV/Substance abuse 27 (1.9%). Prevalence of positive x-ray was divided into few groups. In age group, elderly has highest prevalence followed by adult and children. According to gender, male has higher prevalence than female. If according to ethnicity, Chinese has highest prevalence of positive chest x-ray among all ethnic. Symptomatic people have higher prevalence if compared to asymptomatic. Among high risk group individual, smoking has highest prevalence of positive chest x-ray (28%) followed by HIV/Substance abuse (25.9%), ESRF/COAD (24.2%), ‘Other unspecified’ (21%), Institutionalized (16.9%), Diabetes (12.6%) and Contacts (7.1%). After other cofounders were adjusted, the important risk factors are age AOR (95% CI) 1.03 (1.01-1.04), symptoms AOR (95% CI) 3.8 (2.72-5.50), institutionalised AOR (95% CI) 2.1 (1.09-4.25) and HIV/Substance abuse, AOR (95% CI) 3.6 (1.35-10.0). The discovery of positive chest x-ray during screening for high risk groups affected by factors such as age, and symptoms of TB. Among the twelve-risk factors that have been studied, two risk factors have been identified as an important factor that should be given priority which are institutionalized and HIV/Substance abuse. Consequently, this will facilitate the screening to be carried out more efficiently.